Customers’ Reviews on Social Media and Purchase Decision: The Moderating Role of Age - Rai, Anu; KC, Sadikshya; Poudel, Prakriti; Jha, Priyanka Kumari; Chaudhary, Aruna; Lapcha, Shitesh; Subedi, Purushottam (International Journal of Atharva, 2026)
In the digital marketplace, social media reviews have become a critical source of information for consumers. While their general influence on purchase decisions is well-established, it remains less clear whether this influence is uniform across all consumer demographics. This study specifically investigates the role of age as a potential moderator in the relationship between social media reviews and purchase decisions. This study employed a quantitative, causal-comparative design. Data were collected from 193 participants, selected via convenience sampling, using a structured questionnaire. The instrument demonstrated satisfactory reliability as confirmed by Cronbach’s Alpha. The analysis revealed a strong, positive, and statistically significant relationship between social media reviews and purchase decisions. The overall regression model was significant and explained a substantial portion of the variance in purchase behavior. However, the interaction term between social media reviews and age was not statistically significant, indicating that the strength of the relationship between reviews and purchase decisions does not change with the consumer’s age. The findings confirm that social media reviews are a powerful and significant predictor of purchase decisions. However, age does not act as a moderating variable in this relationship. The impact of reviews is consistent across the different age groups within the studied population, suggesting that the persuasive power of social media word-of-mouth is a universal factor, at least among younger adults.